2017
DOI: 10.7717/peerj.3965
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescence characterization of spinal cord dorsal horn microglia and astrocytes in horses

Abstract: The role of glial cells in pain modulation has recently gathered attention. The objective of this study was to determine healthy spinal microglia and astrocyte morphology and disposition in equine spinal cord dorsal horns using Iba-1 and GFAP/Cx-43 immunofluorescence labeling, respectively. Five adult horses without visible wounds or gait alterations were selected. Spinal cord segments were obtained post-mortem for immunohistochemical and immunocolocalization assays. Immunodetection of spinal cord dorsal horn … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
1
6
0
2
Order By: Relevance
“…In this study, normal astrocytes (grade 0) appeared as staining in a range of 0 to 30 astrocytes/×200 magnification that were well-ramified with minimal contact between cells and tightly connected with blood vessels as also described in the spinal cord of horses by Meneses et al (27) and in fibrous astrocytes from the cerebral cortex in control horses from Regina et al (28). Studies in other animal species describe a similar morphology in non-altered CNS of dogs (29), mice (30), and rats (31), but cattle have a higher number of GFAP+ cells and nonaltered astrocytes approximate morphologically to our grade 1 for horses (32).…”
Section: Immunohistochemical Demonstration Of Equine Astrocytessupporting
confidence: 82%
“…In this study, normal astrocytes (grade 0) appeared as staining in a range of 0 to 30 astrocytes/×200 magnification that were well-ramified with minimal contact between cells and tightly connected with blood vessels as also described in the spinal cord of horses by Meneses et al (27) and in fibrous astrocytes from the cerebral cortex in control horses from Regina et al (28). Studies in other animal species describe a similar morphology in non-altered CNS of dogs (29), mice (30), and rats (31), but cattle have a higher number of GFAP+ cells and nonaltered astrocytes approximate morphologically to our grade 1 for horses (32).…”
Section: Immunohistochemical Demonstration Of Equine Astrocytessupporting
confidence: 82%
“…Under conditions such as parenchymal injury, degeneration or infection, the morphology, phenotype and function of microglia change significantly, 68 such as switching from ramified to amoeboid shapes and showing higher expression levels of the specific microglial marker Iba-1. 69,70 Because previous studies have found that after 5 days of infection with RH strain T. gondii, there is an infiltration of pseudocysts occupied by tachyzoite (s) in the brain cortical tissue and strong inflammatory infiltration, 71 we further studied the status of microglia cells and the content of pro-inflammatory cytokines. Consistent with the results of Hwang et al, 72 in addition to the enhanced expression of Iba-1 in microglia in acute T. gondii infection, the expression of pro-inflammatory cytokines (IFNγ and TNFα) were also increased.…”
Section: Discussionmentioning
confidence: 99%
“…В литературе, посвященной оценке реакции спинного мозга на патологические стимулы, отмечено присутствие двух морфофункциональных типов микроглиоцитов, а также промежуточных форм [62][63][64][65]. Традиционно в спинном мозге выделяют покоящиеся (рамифицированные), активированные (амебоидные) микроглиоциты и переходные формы.…”
Section: микроглия в нормеunclassified
“…При активации микроглии, которая вызвана повреждением СМ, происходит сокращение количества и протяженности клеточных отростков. В конечном итоге клетки приобретают амебоидную форму, что сопровождается продукцией биоактивных молекул, тем самым способствуя активизации воспалительных реакций и борьбе с повреждающими агентами [62][63][64][65]. Известно, что амебоидная микроглия представляет собой высокомобильные фагоцитирующие клетки, участвующие в презентации антигена.…”
Section: микроглия в нормеunclassified